Comparative Toxicity Assessment of Kratom Decoction, Mitragynine and Speciociliatine Versus Morphine on Zebrafish (Danio rerio) Embryos - Damodaran, Thenmoly; Chear, Nelson Jeng-Yeou; Murugaiyah, Vikneswaran; Mordi, Mohd Nizam; Ramanathan, Surash (Frontiers in Pharmacology, 2021)
Background: Kratom (Mitragyna speciosa Korth), a popular opioid-like plant holds its therapeutic potentials in pain management and opioid addiction. However, there are growing concerns about the safety or potential toxicity of kratom after prolonged use. Aim of the study: The study aimed to assess the possible toxic effect of kratom decoction and its major alkaloids, mitragynine, and speciociliatine in comparison to morphine in an embryonic zebrafish model. Methods: The zebrafish embryos were exposed to kratom decoction (1000 to 62.5 µg/mL), mitragynine, speciociliatine, and morphine (100 to 3.125 µg/mL) for 96-hour post-fertilization (hpf). The toxicity parameters, namely mortality, hatching rate, heart rate, and morphological malformations were examined at 24, 48, 72, and 96 hpf. Results: Kratom decoction at a concentration range of ≥ 500 µg/mL caused 100% mortality of zebrafish embryos and decreased the hatching rate in a concentration-dependent manner. Meanwhile, mitragynine and speciociliatine exposure resulted in 100% mortality of zebrafish embryos at 100 µg/mL. Both alkaloids caused significant alterations in the morphological development of zebrafish embryos including hatching inhibition and spinal curvature (scoliosis) at the higher concentration. Exposure to morphine-induced significant morphological malformations such as pericardial oedema, spinal curvature (lordosis), and yolk edema in zebrafish embryos. Conclusion: Our findings provide evidence for embryonic developmental toxicity of kratom decoction and its alkaloids mitragynine and speciociliatine at the higher concentration, thus suggesting kratom consumption may have potential teratogenicity risk during pregnancy that warrants further investigations.